Pemanfaatan Lactobacillus plantarum 1 dan Pewarna Alami Berbahan Nabati Dalam Pembuatan Tapai Probiotik - Yusmarini Yusmarini; Shanti Fitriani; Vonny Setiaries Johan; Rahmayuni Rahmayuni; Vita F. Artanti (Agricultural Faculty, 2020)
Tapai is one of the typical Indonesian fermented products. This research utilized Lactobacillus plantarum 1 RN2-53 and natural dyes made from plants in the production of cassava tapai. The objectives of this research were to improve the quality of probiotic cassava tapai and to obtain the chemical, microbiological and sensory characteristics of the cassava tapai. Natural dyes used were purple sweet potato extract, red dragon fruit extract and narrow-leaf pleomele extract. The results showed that cassava tapai made with the addition of Lactobacillus plantarum 1 RN2-53 and the addition of natural dyes from plants had different chemical and microbiological characteristics. Tapai made with the addition of red dragon fruit extract generally had a lower pH value and a higher total titrated acid compared to tapai made with the addition of purple sweet potato extract and narrow-leaf pleomele extract, but the alcohol content of tapai made with the addition of purple sweet potatoes extract was higher than the others. The number of lactic acid bacteria was around 109 and had met the probiotic food criteria.